Culture and food security - Elena Briones Alonso; Lara Cockx; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
This paper reviews available cross-disciplinary evidence on how culture affects food security. We discuss the impact of culture on all four dimensions (availability, access and choice, utilization, and stability). Although there is large heterogeneity in the size and breadth of available evidence, with research often biased toward high-come countries, it is clear that how and why we obtain, process, prepare, and eat food is influenced by culture in various ways. In addition, gender, family, and decision-making power play a critical role in the impact of culture. The dynamics of culture as well as the magnitude and relative importance of cultural effects in the context of food security are still poorly understood. Nevertheless, there remains ample scope for improving food security policy by taking culture better into account.
Keywords: 330; Culture; Food security; Nutrition